ISOLASI DAN IDENTIFIKASI Trichoderma spp. DARI RHIZOSFER TANAMAN JATI (Tectona grandis Linn.) DI TAMAN HUTAN RAYA PROF. IR. HERMAN YOHANES, DESA KOTABES, KECAMATAN AMARASI KABUPATEN KUPANG - Neto, Petrus Dae; Henuk, Julinda B. D.; Mau, Astin Elise (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
Teak (Tectona grandis Linn.) is a type of forestry plants that has high economic value. Trichoderma spp. is a soil microorganism that is naturally capable of attacking pathogenic fungi and beneficially for plants. This study aims to identify and find out the types of Trichoderma spp. as a biological control agent in the rhizosphere area of teak plants (Tectona grandis Linn.), in Prof. Ir. Herman Yohanes Forest Park, Kotabes Village, Amarasi District, Kupang Regency. This research took place from May to September 2021. Sample tree selection is done using the purposive sampling method, by determining the sample point on a healthy plant. 5 trees were taken as samples and each sample tree is taken 4 points just below the canopy as a soil sampling point. Isolation and identification were carried out at the Laboratotium of Plant Diseases, Faculty of Agriculture, University of Nusa Cendana. Fungal inoculums observed their culture characteristics macroscopically and morphological characteristics microscopically. Cultural and morphological characteristic data are analyzed descriptively and presented in the form of descriptions and images compared to literature to ascertain their identity. The results found 2 species of Trichoderma namely T. citrinoviride, T. reesei.